Recent and Ancient Signature of Balancing Selection around the S-Locus in Arabidopsis halleri and A. lyrata - Roux, Camille; Pauwels, Maxime; Ruggiero, Maria-Valeria; Charlesworth, Deborah; Castric, Vincent; Vekemans, Xavier (Molecular biology and evolution, 2013)
Balancing selection can maintain different alleles over long evolutionary times. Beyond this direct effect on the molecular targets of selection, balancing selection is also expected to increase neutral polymorphism in linked genome regions, in inverse proportion to their genetic map distances from the selected sites. The genes controlling plant self-incompatibility are subject to one of the strongest forms of balancing selection, and they show clear signatures of balancing selection. The genome region containing those genes (the S-locus) is generally described as nonrecombining, and the physical size of the region with low recombination has recently been established in a few species. However, the size of the region showing the indirect footprints of selection due to linkage to the S-locus is only roughly known. Here, we improved estimates of this region by surveying synonymous polymorphism and estimating recombination rates at 12 flanking region loci at known physical distances from the S-locus region boundary, in two closely related self-incompatible plants Arabidopsis halleri and A. lyrata. In addition to studying more loci than previous studies and using known physical distances, we simulated an explicit demographic scenario for the divergence between the two species, to evaluate the extent of the genomic region whose diversity departs significantly from neutral expectations. At the closest flanking loci, we detected signatures of both recent and ancient indirect effects of selection on the S-locus flanking genes, finding ancestral polymorphisms shared by both species, as well as an excess of derived mutations private to either species. However, these effects are detected only in a physically small region, suggesting that recombination in the flanking regions is sufficient to quickly break up linkage disequilibrium with the S-locus. Our approach may be useful for distinguishing cases of ancient versus recently evolved balancing selection in other systems.